2018
DOI: 10.3390/molecules23102468
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Tyrosyl-DNA Phosphodiesterase 1 Inhibitors That Contains the Octahydro-2H-chromen-4-ol Scaffold

Abstract: Tyrosyl-DNA phosphodiesterase 1 (Tdp1) is a DNA repair enzyme that mends topoisomerase 1-mediated DNA damage. Tdp1 is a current inhibition target for the development of improved anticancer treatments, as its inhibition may enhance the therapeutic effect of topoisomerase 1 poisons. Here, we report a study on the development of a novel class of Tdp1 inhibitors that is based on the octahydro-2H-chromene scaffold. Inhibition and binding assays revealed that these compounds are potent inhibitors of Tdp1, with IC50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Additionally, potent inhibitory activity was found for derivatives containing adamantane. Bile acid amide 21 inhibited Tdp1 with IC 50 = 0.47 µM [44], whilst octahydro-2H-chromen-4-ol derivative 22 IC 50 was 1.24 µM (see Figure 2) [45]. It was also demonstrated that compounds combining adamantane/heteroadamantane and monoterpene fragments are active against Tdp1 [46,47].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, potent inhibitory activity was found for derivatives containing adamantane. Bile acid amide 21 inhibited Tdp1 with IC 50 = 0.47 µM [44], whilst octahydro-2H-chromen-4-ol derivative 22 IC 50 was 1.24 µM (see Figure 2) [45]. It was also demonstrated that compounds combining adamantane/heteroadamantane and monoterpene fragments are active against Tdp1 [46,47].…”
Section: Introductionmentioning
confidence: 94%
“…Intrinsic protein fluorescence assay were conducted according to the protocol as described in references [35,45,49]. The concentrations of recombinant Tdp1 and ligand were 10 µM and 1 mM, respectively.…”
Section: Binding Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the activity assay that we reported above, we wanted to confirm the interactions between compound 3ba and Tdp1 before progressing to in vivo studies. Using an intrinsic tryptophan fluorescence quenching assay that we previously applied to study the binding interactions of Tdp1 and its inhibitors [43,45,48,49,52], we evaluated the binding of compound 3ba to recombinant Tdp1. Clear quenching of the Tdp1 intrinsic fluorescence was observed upon the addition of 3ba (Supplementary Figure S1).…”
Section: Biologymentioning
confidence: 99%
“…To date, many Tdp1 inhibitors have been identified. A major class of Tdp1 inhibitors comprises those based on natural products including usnic acid derivatives [41][42][43][44][45], coumarins [46], adamantanes [47][48][49], nucleoside analogs [50], dehydroabietylamine derivatives [51], chromenes [52], bile acids derivatives [53], and fungal products [54][55][56]. There are also early reports of Tdp1 inhibition based on diamidines [57], antibiotics [58,59], steroids [60], and other compounds [61].…”
Section: Introductionmentioning
confidence: 99%